ANALISA RASIO LIKUIDITAS DAN PROFITABILITAS TERHADAP KINERJA KEUANGAN PT.KALBE FARMA Tbk - Saragi, Emmi Fernando; Oktavianti, Oktavianti; Ariyati, Yannik (University of Riau Kepulauan, 2015)
Base background that is presented, writer concludes its problem formulation which is how liquidity ratio influence ( current ratio) and profitability ratio( profit margin ) to financial performance PT. Kalbe Farma Tbk ( Return On Asset ) on year 2005 until 2011. The purpose of observational it is subject to be know finance performance ( Return On Asset ) on PT. Kalbe Farma Tbk is seen from liquidity ratio ( curent ratio) and profitability ratio ( profit margin ) on year 2005 until 2011. In this research, writer use secondary data type. Data source is gotten of Indonesia Stock Exchange ( BEI ) notably on PT. Kalbe Farma Tbk of year 2005 2011 through website www. idx. co. id. Data collecting method is document or studi is acquired bibliography of book literature and also other datas that gets bearing with observational. Observational method by methodics descriptive quantitative which is with get data and information is next at analysis corresponds to fact as numeral as to test hypothesis already being established and for its examination result use SPSS program (Statistisal Product and service Solution) version 20. Of writer research result take that conclusion current ratio and profit margin goes together positive ascendant and signifikan to financial performance PT. Kalbe Farma Tbk.